Oil extraction from Calophyllum inophyllum L. via Soxhlet extraction: Optimization using response surface methodology (RSM) - Shamsuddin, N.M. (Institute of Electrical and Electronics Engineers Inc., 2015)
Biodiesel is an alternative biodegradable and nontoxic fuel, which is free of sulfur and aromatics. Several non-edible oils such as Madhuca indica, Jatropha curcas, Pongania pinnata and Calophyllum inophyllum L. has been investigated experimentally, are found to be suitable for biodiesel production. In this study, Response Surface Method (RSM) based on Central Composite Design (CCD) was applied to determine the optimum condition of oil extraction from Calophyllum inophyllum L. oil via Soxhlet extraction. Three variables studied were solvent to seed ratio (ml), extraction time (hr), and drying time (hr) with total of 15 individual experiments conducted for optimizing the combination effects of those variables. The mathematical model developed was found to be adequate and statistically accurate to predict the optimum yield of Calophyllum inophyllum L. oil. From the analysis of variance (ANOVA), the significance of various factors and their influences were identified. The optimum condition identified was solvent to seed ratio of 56.82 ml/g, extraction time of 2.55 hours, and drying time for the kernel of 6.82 hours. With high percentage of oil yield from Calophyllum inophyllum L. kernel, it serves as a very promising feedstock for biodiesel production. Â© 2015 IEEE.